The Relationship between Knowledge and Attitudes with Financial Literacy Program Among Secondary School - Razali, Nur Hanisah Mohd; Mustafa, Nik Nur Shafika; Rahman, Nor Hadaliza Abd; Noah, Roha Mohamed; Johan, Nurul Haida (Advances in Social Sciences Research Journal, 2024)
This study was conducted to determine the relationship between students' reaction towards the financial literacy education program with the knowledge and attitudes acquired after the program. This study is also to determine differences in knowledge and attitudes and skills of students before and after the program. Quantitative research design involved the respondents' secondary school. Questionnaires were distributed among secondary school students and analyzed using the descriptive statistic, paired t-test and correlation. The findings show that student reaction towards the financial literacy program was good and there is a significant difference between knowledge and attitude before and after the program undertaken.